Racism among white Afrikaner adolescents: The challenge of I-Thou (Buber) relations - Dyk, Sebastiaan van (HTS teologiese studies, 2020)
This article was derived from my doctoral thesis, ‘Post-apartheid racism among Afrikaans speaking urban adolescents: A narrative-pastoral reflection’. The impetus for this study was the seemingly increasing occurrences of racism amongst post-apartheid Afrikaans-speaking urban adolescents in South Africa by taking a narrative practical theological perspective on the matter to help build meaningful cross-cultural dialogue. This study explored the level of dialogue of the participants using a postfoundational paradigm. Two questions guided the investigation: (1) How deeply embedded are objectifying of cross-cultural relationships? (2) How can we instigate honest dialogue aiding us in being more aware of our biases to embrace diversity and going forward as a unity in diversity? This study was conducted in 2016 amongst white Afrikaans-speaking urban adolescents living in Pretoria-East, South Africa. I had four group conversations (A, B, C and D) with my co-researchers (research participants), with six to eight adolescents per group. I made use of certain empirical research methods, such as narrative interviewing and group discussions. From an epistemological perspective, a postfoundational, social constructionist perspective, including an auto-ethnographical approach, was followed. The research indicated that Afrikaner adolescents could live life unquestioned from a position of power and objectivity that was culturally inherited. It was found that by objectifying relationships (I-It), diverse engagement becomes almost impossible. Consequently, this article advocates for a dialogical (I-Thou) approach towards building relationships in a context where people feel vulnerable and shameful, have fears, but also gain trust to contribute to meaningful dialogue with ‘others’.